Room temperature control of spin states in a thin film of a photochromic iron(ii) complex. Issue 3 (21st March 2018) - Poggini, Lorenzo; Milek, Magdalena; Londi, Giacomo; Naim, Ahmad; Poneti, Giordano; Squillantini, Lorenzo; Magnani, Agnese; Totti, Federico; Rosa, Patrick; Khusniyarov, Marat M.; Mannini, Matteo
Abstract : Thin films of a molecular spin crossover iron(ii ) complex featuring a photochromic diarylethene-based ligand have been grown by sublimation in ultra-high vacuum on Au(111) and investigated by photoelectron spectroscopies. Abstract : Thin films of a molecular spin crossover iron(ii ) complex featuring a photochromic diarylethene-based ligand have been grown by sublimation in ultra-high vacuum on an Au(111) single crystal, and investigated by X-ray and UV photoelectron spectroscopies. Temperature-dependent studies demonstrate that the thermally induced spin crossover behaviour is preserved in thin films. The photochromic ligand deliberately integrated into the complex allows photoswitching of the spin states of this iron(ii ) complex at room temperature, and this photomagnetic effect is still observed in 5 nm thick sublimated films. Thus, this work opens new horizons and pushes bistable spin crossover systems closer to prospective applications in molecular electronics and molecular spintronics devices functioning at room temperature.